A Simple and Scalable Approach for Fabricating High-Performance Superparamagnetic Natural Cellulose Fibers and Papers. (15th March 2021) - Mashkour, Mahdi; Mashkour, Mozhdeh
Graphical abstract: Highlights: A new combined method is proposed for fabricating high-performance SPNCFs. The SPNCFs were prepared by kraft pulping of pre-prepared magnetic wood. The outer surface of SPNCFs was free from the magnetic nanoparticles. Papers made of the SPNCFs showed good appearance, printability and tensile properties. Abstract: This study introduces a new combined method of wood impregnation and chemical pulping processes leading to the production of superparamagnetic cellulose fibers with a magnetic nanoparticle-free outer surface. First, magnetic wood chips (MWCs) were prepared by in situ synthesizing of magnetite (Fe3 O4 ) nanoparticles during the wood impregnation process. The MWCs were then converted into magnetic fibers by kraft pulping. The results showed that the resulting magnetic fibers had an outer surface comparable to that of non-magnetic fibers while showing superparamagnetic behavior. The XRD results confirmed that the in situ synthesized magnetic nanoparticles were magnetite. Papers made from the new type of magnetic cellulose fibers had much more desirable tensile properties, appearance, and printability than papers made from conventional magnetic cellulose fibers, comparable to those made from non-magnetic fibers.